2011
DOI: 10.1007/bf03337763
|View full text |Cite
|
Sign up to set email alerts
|

Seated stepping exercise in a dual-task condition improves ambulatory function with a secondary task: a randomized controlled trial

Abstract: This RCT suggests that the seated stepping exercise is more effective at improving ambulatory function in DT conditions than in ST conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 20 publications
0
52
0
Order By: Relevance
“…Table 1 for the search strategy). Based on titles, studies in languages other than English were excluded (n=1; 78) along with case reports (n=4; [1,6,47,65]), studies not concerning motor training interventions to improve standing or walking tasks (n=17; [7, 8, 10, 13, 18, 42-44, 46, 49, 54, 64, 68, 71, 81, 90, 91, 97]), not using a pre-post test or agecomparison design, (n=4: [22,40,89,98]), not conducted with older adults (n=1; [37]) or not focusing healthy older adults (n =6; [3,22,24,82,99,100]) were also excluded (cf. Table 5 for excluded studies in the Annex).…”
Section: Selection Criteriamentioning
confidence: 99%
“…Table 1 for the search strategy). Based on titles, studies in languages other than English were excluded (n=1; 78) along with case reports (n=4; [1,6,47,65]), studies not concerning motor training interventions to improve standing or walking tasks (n=17; [7, 8, 10, 13, 18, 42-44, 46, 49, 54, 64, 68, 71, 81, 90, 91, 97]), not using a pre-post test or agecomparison design, (n=4: [22,40,89,98]), not conducted with older adults (n=1; [37]) or not focusing healthy older adults (n =6; [3,22,24,82,99,100]) were also excluded (cf. Table 5 for excluded studies in the Annex).…”
Section: Selection Criteriamentioning
confidence: 99%
“…[21] , and 2 studies involved seated exercises [55,56] . Cognitive activities used in the dual-task interventions included counting forwards [16,47] or backwards [5,47,50] , reciting letters of the alphabet [16] , naming words in a particular category [5,16,50,55,56] , spelling backwards [5,50] , and n-back and serial position working memory tasks [51] . Motor-motor dual-tasks as part of the interventions were not always specified but included walking while buttoning and unbuttoning or carrying a tray with glasses of water [47] and balancing while catching and throwing a ball [21] .…”
Section: Sample Characteristicsmentioning
confidence: 99%
“…Indeed, of the 21 studies, 17 assessed gait performance using walking speed [16,18,[44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] . Other measures of gait performance included gait variability (e.g., variability in stride/step duration or stride length) [21,43,45,51,53,54] , cadence [17,18,47,[52][53][54] , step duration [17,18,54] , stride duration [18,52] , step length [17,18,45,47] , stride length [18,52] , single support duration [18,52] , double support duration [18,47,53,54] , support base [53] , distance walked in 1 min [42] , and number of steps over 10 m …”
Section: Dual-task Outcome Measuresmentioning
confidence: 99%
“…The results of this trial suggested that the seated stepping exercise program was indeed effective at improving DT walking ability (Yamada et al, 2010a).…”
Section: Seated Stepping Exercisementioning
confidence: 82%
“…DT walking is associated with falls in the robust elderly population, and thus this population should be given the rhythmic stepping exercise (Yamada et al, 2011e). DT walking and muscle strength are associated with falls in the intermediate elderly population, and thus this population should be given the seated stepping exercise (Yamada et al, 2010a). Muscle strength and DT walking are associated with falls in the pre-frail elderly population (Yamada et al, 2010b) and thus this population should be given the trail walking exercise.…”
Section: Different Factors Related To Fall Incidentsmentioning
confidence: 99%